Effect of time-dependent inter-particle interaction on the dynamics of a dissipative double-well Bose-Einstein condensate - Rajagopal, Kalai Kumar; Zhang, Ruqi (Communications in Physics, 2024)
In this paper, we study the dynamics of a dissipative double-well BEC driven by sinusoidally oscillating time-dependent inter-particle interaction. The phase space of the system is illustrated physically by its population imbalance and phase difference. The macroscopic dynamics of the model are generated within the Mean-field limit neglecting a single moment for random noise but their two-point noise-noise correlation persists. Equilibrium stability fixed points are observed for systems subjected to constant inter-particle interaction. The time-dependent (sinusoidal) inter-particle interactions in contrast, however, drive the system into the complex dynamic. The system’s phase-space dynamics is sensitive to small changes in the initial conditions. We found dissipation concurrent with large driving amplitude or frequency of inter-particle interaction enhances the route to chaos.